Healthy lifestyle among Malaysian students - Khairul Anuar, Nur Farah Batrisyia; Mohd Noramin, Nur Nasuha; Azlan, Najihah; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Healthy lifestyle have been a major concern for Malaysian government. Many activities and campaign has been done to promote healthy lifestyle among Malaysian people. There are various factors that influence a healthy lifestyle. Understanding the factors that impact the health and well-being of Malaysian students is crucial for developing effective strategies to promote healthier lifestyles and enhance their overall well-being. Therefore, this study will only focusing on healthy lifestyle among Malaysian Students. The aim of this study is to identify awareness among Malaysian students about the importance of leading a healthy lifestyle and importance of fitness and healthy lifestyle among students. From the survey that have been done among all universities students in Malaysia, it is found out that most Malaysian students agree that healthy lifestyle lead to healthier life. Most of them think fasting and dieting are the best way to get a healthy body. Therefore, by prioritizing a creasing awareness, regular physical activity, dietary habit, mental health and stress, students can improve their overall well-being, academic performance, and prospects.